Shoulder angiosarcoma. Interscapulotor´acic disarticulation - Otero, José Pedro; Cassinelli, Juan Francisco; Delgado, Bolívar (Cirugía del Uruguay, 2021)
The authors presents a angiosarcoma of the shoulder successfully treated by radioteraphy, local resection and scapulothoracic desarticulation. They do considerations about histogenetics and byology of this rare tumors. They remarks that widP surgical resection in the first operation is the best procedure for cure.